Constitutive activation of SHP2 protein tyrosine phosphatase inhibits ICSBP-induced transcription of the gene encoding gp91(PHOX) during myeloid differentiation - Zhu, Chunliu (2007)
The IFN consensus sequence-binding protein (ICSBP; also referred to as IFN regulatory factor 8) is a transcription factor which is expressed in myeloid and B cells. In previous studies, we found that ICSBP activated transcription of the gene encoding gp91(PHOX) (the CYBB gene), a rate-limiting component of the phagocyte respiratory burst oxidase expressed exclusively after the promyelocyte stage of myelopoiesis. Previously, we found that CYBB transcription was dependent on phosphorylation of specific ICSBP tyrosine residues. Since ICSBP is tyrosine-phosphorylated during myelopoiesis, this provided a mechanism of differentiation stage-specific CYBB transcription. In the current studies, we found that ICSBP was a substrate for Src homology-containing tyrosine phosphatase 2 (SHP2-PTP) in immature myeloid cells but not during myelopoiesis. Therefore, SHP2-PTP inhibited CYBB transcription and respiratory burst activity in myeloid progenitor cells by dephosphorylating ICSBP. In contrast, we found that ICSBP was a substrate for a leukemia-associated, constitutively active mutant form of SHP2, described previously, throughout differentiation. Consistent with this, constitutive SHP2 activation blocked ICSBP-induced CYBB transcription and respiratory burst activity in differentiating myeloid cells. ICSBP-deficiency and constitutive SHP2 activation have been described in human myelodysplastic syndromes. As these two abnormalities may coexist, our results identified a potential molecular mechanism for impaired phagocyte function in this malignant myeloid disease.